Diaspora Hadrami di Asia Tenggara - Subhan, Arief (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2002)
This book under review is basically in the same line as the above mentioned book it focus to the roles the Hadrami held in the destination countries of their diaspora. The difference lies in the fact that this book concentrated its discussion to the Hadrami diaspora in Southeast Asia. This present book, edited by Huub de Jong and Nico Kaptein, originates from a workshop held in Leiden (1997),